1988
DOI: 10.1016/0014-5793(88)80024-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a tetrasialylated monofucosylated tetraantennary N‐linked carbohydrate chain in human platelet glycocalicin

Abstract: Glycocalicin (140 kDa), the main constituent of the glycoprotein Ib a-chain (150 kDa) of the human platelet membrane, contains 4 putative N-glycosylation sites. For the structural analysis of the N-glycosidic carbohydrate chains of glycocalitin, the glycoprotein has been subjected to the hydrazinolysis procedure. The acidic carbohydrate chains obtained were fractionated by ion-exchange chromatography on DEAE-Sephadex A-25, and subsequently analyzed by sugar analysis, anion-exchange chromatography on Mono Q HR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The carbohydrate structures linked to GPIbα include N- (Korrel et al, 1988) and numerous O-linked carbohydrates throughout the membrane-proximal mucin-like core (Korrel et al, 1984). The N-linked carbohydrates are large, complex, tetraantennary compounds, with terminal branches that consist of NeuAcα ( As expected, GST alone did not bind any of the synthesized carbohydrates (Fig.…”
Section: The Brs Of Gspb and Hsa Bind Different Subsets Of Sialylatedsupporting
confidence: 60%
See 1 more Smart Citation
“…The carbohydrate structures linked to GPIbα include N- (Korrel et al, 1988) and numerous O-linked carbohydrates throughout the membrane-proximal mucin-like core (Korrel et al, 1984). The N-linked carbohydrates are large, complex, tetraantennary compounds, with terminal branches that consist of NeuAcα ( As expected, GST alone did not bind any of the synthesized carbohydrates (Fig.…”
Section: The Brs Of Gspb and Hsa Bind Different Subsets Of Sialylatedsupporting
confidence: 60%
“…The carbohydrate structures linked to GPIbα include N ‐linked carbohydrates within the N‐terminal globular domain (Korrel et al ., 1988) and numerous O ‐linked carbohydrates throughout the membrane‐proximal mucin‐like core (Korrel et al ., 1984). The N ‐linked carbohydrates are large, complex, tetraantennary compounds, with terminal branches that consist of NeuAcα(2‐3)Galβ(1‐4)GlcNAc [α(2‐3) sialyllactosamine] or NeuAcα(2‐6)Galβ(1‐4)GlcNAc [α(2‐6) sialyllactosamine].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of the platelet glycoprotein GPIbα identified a core 2 hexasaccharide comprised of sialyl-T antigen with β1–6 glycosidic linkage between the GlcNAc in 3'-sialyllactosamine Siaα2–3Galβ1–4GlcNAc and the core GalNAc in the sialyl-T antigen 42, 43 (this structure is shown in the conceptual model in Fig. 11B).…”
Section: Discussionmentioning
confidence: 89%
“…The GPIb␣ N-terminal domain contains the di-, tri-, and tetra-antennary N-linked glycans, 44,45 whereas O-linked glycans reside within the C-terminal domain. 46,47 It is probable that in vivo and in vitro removal of platelets occurs via exposed ␤Gal residues on N-linked glycans rather than on O-linked glycans, consistent with the shown effects of ligand valency (tetra-, Ͼ tri-, Ͼ di-, Ͼ mono-antennary) and sugar spacing (20 Å Ͼ 10 Å Ͼ 4 Å) on glycan binding to ASGPRs.…”
Section: Discussionmentioning
confidence: 99%